6th LICMAS 2022 Book of Abstracts - Atia, Ahmed (AlQalam Journal of Medical and Applied Sciences, 2022)
6th LICMAS 2022 Proceeding PROCEEDING OF THE 6TH LIBYAN INTERNATIONAL CONFERENCE ON MEDICAL, APPLIED, AND SOCIAL SCIENCES 2022 ASSEMBLED AND EDITED BY Asst Prof. Ahmed Atia, Center of Research and International Cooperation, University of Tripoli Alahlia, Libya This book contains the abstract of 81 research presented by participants from different countires, such as; Libya, Iraq, Sudan, Algeria, Morocco, Senegal, Austria.